The True Amino Acid Digestibility of 15N-Labelled Sunflower Biscuits Determined with Ileal Balance and Dual Isotope Methods in Healthy Humans. Issue 3 (15th December 2021) - Tessier, Romain; Calvez, Juliane; Airinei, Gheorghe; Khodorova, Nadezda; Kapel, Romain; Quinsac, Alain; Galet, Olivier; Piedcoq, Julien; Benamouzig, Robert; Tomé, Daniel; Gaudichon, Claire
ABSTRACT: Background: Sunflower is a promising protein source but data on amino acid (AA) digestibility are lacking in humans. Classically, the determination of AA digestibility requires ileal digesta sampling. The dual isotope method is minimally invasive but has not been compared to the conventional approach. Objectives: This study aimed to determine the true ileal digestibility of sunflower AAs in healthy volunteers who ate biscuits containing 15 nitrogen (N) protein isolate, in comparison with the dual isotope method. Methods: Twelve healthy volunteers (men and women; 40.4 ± 10.5 years old; BMI, 23.7 ± 2.9 kg/m 2 ) were equipped with a naso-ileal tube. For 4 hours, they consumed 9 repeated meals comprising 15 N-sunflower protein biscuits together with 13 carbon (C)-AAs, carried either in chocolate (SUN + Ch; n = 7) or apple puree (SUN + P; n = 5). Ileal digesta and blood were sampled throughout 8 hours after ingestion of the first meal. The 15 N and 13 C AA enrichments were measured in digesta to determine ileal digestibility directly and in plasma to determine lysine and threonine digestibility using the dual isotope method. Differences between methods and between vector groups were analyzed using paired and unpaired t -tests, respectively. Results: The ileal digestibility of sunflower indispensable AAs (IAA) was 89% ± 5.3%, with threonine and lysine having the lowest digestibility. In the SUN + Ch meal, IAA digestibility was 3% below that of SUN + P ( P < 0.05). The mean free 13 C-AA ileal digestibility was 98.1% ± 0.9%. No matter which matrix was used to carry 13 C-AAs, plasma 15 N and 13 C-AA kinetics displayed a 1-hour offset. Digestibility obtained with the dual isotope method (70.4% ± 6.0% for threonine and 75.9% ± 22.3% for lysine) was below the target values. Conclusions: The ileal digestibility of IAAs from a sunflower isolate incorporated in a biscuit was close to 90% in healthy adults. Under our experimental conditions, the dual isotope method provided lower values than the usual method. Further protocol developments are needed to validate the equivalence between both methods. This trial was registered at clinicaltrials.gov as NCT04024605.